Major Anthropogenic Interactions Determining the Conservation Status of Endemic Mammals of Eastern Africa - Tafesse, Israel Sebsibe; Yohannes, Yordanos Berihun (International Journal of Zoology, 2022)
Africa, as a continent of diversity, harbors many cosmopolitan and endemic mammals, 17 of the world’s 20 orders of terrestrial mammals. The Horn of Africa alone harbors nearly 220 mammalian species, including many threatened species. Mammals, particularly endemics ones, are threatened by anthropogenic challenges impacting their abundance, the number of reproductive individuals, and geographic ranges. Human population, in Eastern Africa, has been growing fast, and political and civil unrest aggravate human impacts on the environment. In particular, this study focused on identifying factors that are influencing the conservation status of endemic mammals of Eastern Africa using a multinomial logistic regression model. Agricultural expansion and deforestation threatened vulnerable (AOR: 2.650, p<0.05) and critically endangered species (AOR: 4.763, p<0.05) more than any other factors. Habitat loss persists as a major factor when critically endangered species (AOR: 3.520, p<0.05) are compared to near threatened species. Collectively, threatened species are mainly impacted by habitat loss (AOR: 2.678, p<0.05), agricultural expansion, and deforestation (AOR: 2.376, p<0.05). In the next 50 years, threats to biodiversity are likely to grow as human populations increase. There is no a generalized global model to measure the intensity of agricultural expansion, habitat loss, hunting, and human settlement in the protected areas. Attempts should be made to develop conservation strategies that aim to articulate an array of several conservation threats together across space and time.